Concurrent Persistent Trigeminal and Hypoglossal Artery and Conservative Approach to Right Internal Carotid Artery Aneurysm: A Case Report - Procházka, Viktor; Bradáč, Ondřej; Bubeníková, Adéla; Leško, Róbert; Iiird, Vladimír Beneš; Skalický, Petr (Annapurna Journal of Health Sciences, 2026)
The presence of persistent embryonic arteries such as the trigeminal artery and hypoglossal artery is a rare vascular anomaly, which can predispose to aneurysms due to altered hemodynamics. This case study reported the coexistence of a persistent trigeminal artery (Saltzman type I) and hypoglossal artery with a stable 4-mm aneurysm at the bifurcation of the right internal carotid artery of the patient and discussed management options.